Mute Meaning and Unspoken Struggle Discourse in '27 Steps of May' - Adek Risma Dedees; Raihanah Permata (Program Studi Ilmu Komunikasi Universitas Bakrie, 2020)
A film has a distinctive language in voicing protest. This article discusses how the film '27 Steps of May' speaks in silent scenes and unspoken discourses through a visual narrative covered in meaningful symbols. Using Barthesian semiotic analysis, we capture hidden messages of pain, trauma, suffering, struggle, rebellion, and speechless protests from a victim of sexual violence against patriarchal culture and an unjust social environment. Silence represents sadness as well as futile anger. The emptiness in the victim's expression signifies despair at the stigma and unchanging blame. The gloomy nuance that dominates the narrative in almost every scene is a form of endless bitterness. The minimalist sound effects not only reflect the emptiness of the victim's life, but also the cinematic effort to invite the audience (and society at large, of course) to contemplate together. Victims of sexual violence in Indonesia always experience multiple and lasting repressions: physical, psychological, social, cultural, structural, and even political. This film, with its empathetic spirit towards victims, uses a 'minimalist' visual narrative weapon to fatally shoot our human conscience.